Oligopoly and the theory of games - Friedman, James W. (Amsterdam ; New York : North-Holland Pub. Co. ; New York : sole distributors for the U.S.A. and Canada Elsevier/North-Holland, 1977)
The book aims at providing a basic coverage of oligopoly theory and n-person nonzero sum game theory. The advanced undergraduate, the graduate student or economist who has some mathematics background will find this book very useful.
Includes index.
Includes bibliographical references: p. 301-306.
rpm 19/07/2017
Loans
Keywords: Oligopolies; Oligopolies -- Mathematical models; Game theory